Strategi PT Delfi Limited dalam Mendominasi Pasar Indonesia Tahun 2024 - Siva Yunika; Salsabila Aulia Emelda; Fadhillah Putri Sudrajat; Desi Qodriah Syahfitri; Epa Fauziah; Septianis Afipah (Indo Publishing, 2026)
This article examines the strategy of PT Delfi Limited, a subsidiary of Singapore-based Delfi Limited, in dominating the Indonesian market in 2024. This research is based on the significance of the Indonesian market, which accounts for approximately 63% of the Delfi Group’s total global revenue in fiscal year 2024, a phenomenon that demonstrates remarkable success in market adaptation and penetration. The main research question posed is: “How did PT Delfi Limited’s strategy dominate the market in Indonesia in 2024?” The main theoretical framework used is Dunning’s Eclectic Paradigm (OLI Framework), combined with the key concepts of Local Responsiveness, Corporate Economic Diplomacy, and Social License to Operate. The research method used is descriptive qualitative, involving document analysis. The results show that PT Delfi Limited’s dominance was achieved through a combination of highly responsive product adaptation strategies tailored to local preferences and active corporate economic diplomacy practices. The conclusion emphasises that PT Delfi Limited’s dominance in the Indonesian market in 2024 is the synergistic result of a strong local product adaptation strategy, reinforced by corporate economic diplomacy manoeuvres and efforts to obtain a Social License to Operate.